Neurocranial anatomy of an enigmatic Early Devonian fish sheds light on early osteichthyan evolution - Clement, A; King, B; Giles, S; Choo, B; Ahlberg, P; Young, G; Long, J (eLife Sciences Publications, 2018)
The skull of ‘Ligulalepis’ from the Early Devonian of Australia (AM-F101607) has significantly expanded our knowledge of early osteichthyan anatomy, but its phylogenetic position has remained uncertain. We herein describe a second skull of ‘Ligulalepis’ and present micro-CT data on both specimens to reveal novel anatomical features, including cranial endocasts. Several features previously considered to link ‘Ligulalepis’ with actinopterygians are now considered generalized osteichthyan characters or of uncertain polarity. The presence of a lateral cranial canal is shown to be variable in its development between specimens. Other notable new features include the presence of a pineal foramen, the some detail of skull roof sutures, the shape of the nasal capsules, a placoderm-like hypophysial vein, and a chondrichthyan-like labyrinth system. New phylogenetic analyses place ‘Ligulalepis’ as a stem osteichthyan, specifically as the sister taxon to ‘psarolepids’ plus crown osteichthyans. The precise position of ‘psarolepids’ differs between parsimony and Bayesian analyses.